A survey of IPv6 deployment - Hamid , Erman; Bahaman, Nazrulazhar; Shibghatullah, Abdul Samad; Abdul Malek, Akhdiat (2008)
The global internetworking (or popular known as Internet) has been very aggressively developed in the last recent years. The technologies of Internet including hardware, software, and protocols expand drastically years by years. IPv6 as the most popular Internet Protocol for Internet will be the main focused for this research. This future promising Internet Protocol which is going to replace the current Internet Protocol (IPv4) is in the right track with so many researches being carried out. This research focused a survey of IPv6 deployment all over the globe. This research also converge the research and development of IPv6 speciﬁcally in Malaysia. Although IPv6 technology is very promising, the deployment and development of IPv6 in Malaysia is quite slow compare to other countries. As a conclusion, A survey ofII’v6 came out with a suggestion and solution on how to evoke IPv6 technology in Malaysia.